My experience teaching English to young learners and teenagers: Some reflections - Mahecha Sánchez Rocío (Profile: Issues in Teachers' Professional Development)
In spite of the harsh environment teachers from the official sector have had to work in, teaching English to children and young learners is a challenging, demanding, hard, but pleasant activity. I am going to write about my experience teaching primary and high school, the difficulties I have encountered, and also the satisfaction of doing my best in this profession.

Key words: English-Teaching, Children Second Language Acquisition, Adolescents Second Language Acquisition, Teaching-Primary School, Teaching-High School

A pesar de la difícil situación que han vivido los maestros del sector oficial, la enseñanza de la lengua inglesa a niños y adolescentes es una actividad desafiante, exigente y sumamente gratificante. En las siguientes líneas escribiré sobre mi experiencia en la escuela primaria y secundaria, las dificultades que he encontrado y además, la satisfacción de hacer lo mejor en mi profesión.

Palabras claves: Inglés-Enseñanza, Adquisición de segundo lenguaje en niños, Adquisición de segundo lenguaje en adolescentes, Enseñanza-Escuela primaria, Enseñanza- Escuela secundaria